REGIONAL INEQUALITY ACROSS DISTRICTS IN KALIMANTAN, 2000 – 2012: IS KUZNETS HYPOTHESIS PREVAIL IN KALIMANTAN? - Maria Christina Yuli Pratiwi (Journal of Indonesian Applied Economics, 2017)
The purpose of this study is to investigate the inequality development across the districts in Kalimantan and examine whether Kuznets hypothesis is prevail in Kalimantan. Williamson Index dan Entropy Theil Index are employed in order to analysis the inequality of 55 districts in Kalimantan during 2000-2012. The result of study shows that: (1) Kuznets hypothesis is prevail in Kalimantan; (2) regional inequality in Kalimantan shows an increasing trend for the period of observation. East Kalimantan province gives the largest contribution towards the inequality in Kalimantan.